Àgbó Masquerade Costumes in the Service of Democracy in Nigeria - Adépégba, Kẹ́hìndé; Ogunyale, Nathaniel O.; Sobowale, Tolulope O.; Adepegba, Oluwaseyitan D. (NIU Journal of Humanities, 2024)
There are many masquerade types in Nigeria. Most ethnic groups in Nigeria have their peculiar masquerade varieties performing different socio-cultural and religious functions in the societies. This accounts for the multiplicity of masquerade types in Nigeria. The Yorùbá, an ethnic group, occupying southwestern parts of Nigeria, have masquerade types namely: Egúngún, Epa, Àgbó, Gẹ̀lẹ̀d ẹ , Ìgunnu, Ẹ̀yọ̀ and Agẹmo among others. What differentiates the masquerade types are their unique costumes. For Egúngún, Gẹ̀lẹ̀dẹ, and Àgbó their wooden headdresses, fabric costumes, and other accouterments allow for displays of symbolic images that communicate socio-cultural and religious messages to the beholders. Right from 1999 when the Forth Republic was ushered into the country, masquerade costumes among the Yorùbá, apart from their socio-religious connotations, also serve as media for promoting democratic values among the people. Therefore, the paper examined the symbolic images of some Àgbó costumes in the services of democracy in Lagos State. The study focused on Àgbó masquerade from Àgbowá-Ìkòsì, a coastal Ìjẹ̀bú town in Lagos State. Data for analysis were gathered from primary sources. The data were analysed using formal and contextual methods. The study established that the sacred costumes of Àgbó masquerade are now also veritable media for promoting democratic values and peace in the study area. Keywords: Masquerade costumes, Àgbó, service of democracy, Àgbowá-Ìkòsì